Notes on Early Land Plants Today. 3. Fossombronia ruminata Cargill, a new name for Fossombronia maritima G.A.M.Scott et D.C.Pike ex Cargill, nom. illeg. - Cargill, D. Christine; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2012)
Fossombronia maritima G.A.M.Scott et D.C.Pike (1987: 378) is invalid, as it was described from multiple gatherings. The name was later validated via typification by Cargill in McCarthy (2003: 114) as Fossombronia maritima G.A.M.Scott et D.C.Pike ex Cargill.